Prediction of rain rate distribution with time delay based on measured 1-min rain intensity data to mitigate fades on satellite link - Alam, Md Moktarul; Islam, Md. Rafiqul; Salam, M. A.; Muhammad, Norhafizah (Institution of Engineering and Technology, 2018)
Earth to satellite communications are moving towards higher frequency bands in future which are more sensitive to environment. Rain causes severe degradation in performances at higher frequency bands specially in tropical regions. Several mitigation techniques are proposed by researcher to design reliable system. Time diversity is one of the potential candidate for it. However, time diversity analysis requires measured rain attenuation data. For future high frequency link design those data are not available at most of the places. This paper proposes a method to utilize 1-min rain rate to analyse time diversity technique at any desired frequency. In proposed method, it is assumed that rain rate with delay can represent rain attenuation with delay for same period of time at same location. This assumption is valid as long as the attenuation causes due to rain. A model is developed to predict rain rate distribution with delay from annual measured statistics.